2021
DOI: 10.1002/esp.5067
|View full text |Cite
|
Sign up to set email alerts
|

Late‐Quaternary miliolite (biogenic carbonate) deposits and their implications for sea‐level fluctuations and climatic variability

Abstract: The western coast of India (Kachchh) has ubiquitous preservations of Quaternary carbonate deposits popularly known as "miliolites". Field-based detail documentation of the nature and distribution of miliolites supported by sedimentology and scanning electron microscopy (SEM) microtextural studies indicates that the miliolites were primarily deposited by wind as aeolinites and are termed "primary miliolites (PM)". These were subsequently fluvially eroded and deposited and such deposits are termed "secondary mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Thakkar et al (1999Thakkar et al ( , 2001 reported the Quaternary sequences within the rocky mainland in the form of three major episodes as alluvial and colluvial fan deposits as Early Pleistocene, sandy sheets of miliolites with boulders and pebbles as middle Pleistocene and fluvial sand silt and clay with some aeolian deposits of late Pleistocene and Recent age. Later on, various episodes of Late Pleistocene and Holocene sedimentation along various river courses in Kutch Basin are documented and are exploited for reconstructing the history of sea-level changes, climate and tectonics events spanning the last 100 (Maurya et al 2003a(Maurya et al , b, c, 2008(Maurya et al , 2013Khonde et al 2011Khonde et al , 2017aChowksey et al 2010;Das et al 2016aDas et al , b, 2017Das et al , 2020Prizomwala et al 2014aPrizomwala et al , b, 2016aPrizomwala et al , b, 2019Patidar et al 2007Patidar et al , 2008Kundu et al 2010;Bhattacharya et al 2013aBhattacharya et al , b, 2019Ngangom et al 2012Ngangom et al , 2017Ngangom and Thakkar 2016;Thakkar et al 2020a;Durga Prasad et al 2021).…”
Section: Stratigraphymentioning
confidence: 99%
“…Thakkar et al (1999Thakkar et al ( , 2001 reported the Quaternary sequences within the rocky mainland in the form of three major episodes as alluvial and colluvial fan deposits as Early Pleistocene, sandy sheets of miliolites with boulders and pebbles as middle Pleistocene and fluvial sand silt and clay with some aeolian deposits of late Pleistocene and Recent age. Later on, various episodes of Late Pleistocene and Holocene sedimentation along various river courses in Kutch Basin are documented and are exploited for reconstructing the history of sea-level changes, climate and tectonics events spanning the last 100 (Maurya et al 2003a(Maurya et al , b, c, 2008(Maurya et al , 2013Khonde et al 2011Khonde et al , 2017aChowksey et al 2010;Das et al 2016aDas et al , b, 2017Das et al , 2020Prizomwala et al 2014aPrizomwala et al , b, 2016aPrizomwala et al , b, 2019Patidar et al 2007Patidar et al , 2008Kundu et al 2010;Bhattacharya et al 2013aBhattacharya et al , b, 2019Ngangom et al 2012Ngangom et al , 2017Ngangom and Thakkar 2016;Thakkar et al 2020a;Durga Prasad et al 2021).…”
Section: Stratigraphymentioning
confidence: 99%
“…The various episodes of Late Pleistocene and Holocene sedimentation that took place along various river courses in Mainland Kachchh, the Island belts, and Wagad have been documented and are important for reconstructing the history of climate and tectonics spanning the last 100 ka (Figs. 11 and 18c, d) (Maurya et al 2003a(Maurya et al , 2003b(Maurya et al , 2003c(Maurya et al , 2008(Maurya et al , 2013Khonde et al 2011Khonde et al , 2017aKhonde et al , 2017bChowksey et al 2010;Das et al 2016aDas et al , 2016bDas et al , 2017Prizomwala et al 2014aPrizomwala et al , b, 2016aPrizomwala et al , 2016bPrizomwala et al , 2019Patidar et al 2007Patidar et al , 2008Kundu et al 2010;Bhattacharya et al 2013aBhattacharya et al , b, 2019Ngangom et al 2012, Ngangom and Thakkar 2016Makwana et al 2019;Sane et al 2020;Durga Prasad et al 2021).…”
Section: Stratigraphymentioning
confidence: 99%
“…The Kachchh peninsula in western India has patches of these aeolinites, which are primarily bioclastic carbonate deposits termed as ‘miliolites’ (Bhatt, 2003; Carter, 1849; Lele, 1973). Durga Prasad et al (2021) have studied the primary and secondary miliolites in the Kachchh mainland. The primary miliolites were deposited during the Last Glacial Maximum (LGM) period (26–16 ka) in response to enhanced aridity and lowered sea level.…”
Section: Recent Developments In Indian Geomorphology: An Overviewmentioning
confidence: 99%